A Snapshot of MOOCs in Hospitality and Tourism. Issue 2 (2nd April 2016) - Ryan, Peter; Horton-Tognazzini, Laurel; Williams, Alan
ABSTRACT: Massive open online courses (MOOCs) are a significant disruptive innovation in the current higher education environment. Although the media and academia often make sweeping generalizations about MOOCs, ranging from a utopian to dystopian future, such hyperbole about innovations is common and often misguided. Critics focus on poor completion rates, typically less than 10%, whereas pundits laud the massive and global enrollments. This research note helps ground the hyperbole, reviewing MOOCs in the broad discipline of hospitality and tourism and providing a snapshot of the MOOCs currently on offer.